Myc and loss of p53 cooperate to drive formation of choroid plexus carcinoma - Wang, Jun (Cancer Res, 2019)
Choroid plexus carcinoma (CPC) is a rare brain tumor that occurs most commonly in very young children and has a dismal prognosis despite intensive therapy. Improved outcomes for CPC patients depend on a deeper understanding of the mechanisms underlying the disease. Here we developed transgenic models of CPCs by activating the Myc oncogene and deleting the Trp53 tumor suppressor gene in murine neural stem cells or progenitors. Murine CPC resembled their human counterparts at a histological level, and like the hypodiploid subset of human CPC, exhibited multiple whole-chromosome losses, particularly of chromosomes 8, 12 and 19. Analysis of murine and human CPC gene expression profiles and copy number changes revealed altered expression of genes involved in cell cycle, DNA damage response, and cilium function. High-throughput drug screening identified small molecule inhibitors that decreased the viability of CPC. These models will be valuable tools for understanding the biology of choroid plexus tumors and for testing novel approaches to therapy.